The Implementation of Moderation Values in Scouting Activities at SMP Negeri 1 Sukamara - ozi, wahidfachurrozi; Muslimah, Muslimah; Swestyani, Sondra (Institut Agama Islam Negeri (IAIN) Curup, 2024)
Religious moderation refers to a balanced understanding that avoids extremes and excessiveness. The nine principles of religious moderation include intolerance, cultural adaptability, patriotism, anti-violence, deliberation, reform, and leadership, and honesty. This study aims to describe the implementation of religious moderation values in scouting activities at SMP Negeri 1 Sukamara. A qualitative descriptive approach was employed to explore and portray the issue. Data for this research were collected through a combination observation, interviews, and documentation, with source triangulation applied for validation. Then, analysis was conducted, integrating ideas related to moderation, until completion. This reveal that religious moderation values, such patriotism, deliberation, tolerance, and leadership, have implemented through scouting activities. These results underscore the importance of schools paying attention to the application of religion moderation. The school has adopted an approach to instilling attitudes of religious moderation among students by initiating extracurricular scouting activities.